THE APPLICATION OF ISLAMIC LEADERSHIP TO IMPROVE EMPLOYEE PRODUCTIVITY IN ORDER TO MAINTAIN THE PROFITABILITY AFTER THE AUDIT BPJS - Angga Ferwita; Emi Linawati; Barika Isti’anatil Hidayah; Mundakir; Mirrah Sammiyah (Global Journal of Health Administration, 2025)
Objective: The post-claim audit by BPJS has prompted Type C Specialist Hospitals to maintain profits through the implementation of Islamic leadership. Methods: The research was conducted in August- September 2024. This research is a case study using a mixed-methods approach. There were 8 informants, determined using purposive sampling. Data collection techniques included interviews, questionnaires, and documents using sequential explanatory analysis. The Director of the Special Type C Hospital has implemented Islamic leadership principles. The majority of respondents (57.1%) agreed with the implementation of Islamic leadership by the director at the hospital. As a result, the majority of respondents (72.1%) agreed that they were motivated to solve problems and that performance had improved. Additionally, respondents strongly agreed (42.9%) that they became more productive in completing medical record tasks or casemix due to the implementation of Islamic leadership, which encourages working more honestly in accordance with regulations. These efforts resulted in a change in profitability in August of - 18.4%, compared to June of -38.1% in 2024. Results: The director of a Type C Specialised Hospital implemented Islamic leadership, which proved to increase employee productivity and encourage them to work more honestly in accordance with regulations. The implementation of these strategies was associated with a decrease in profitability by 18.4% in August, suggesting a potential adverse impact on financial performance during the period. Conclusion: The implementation of Islamic leadership increases productivity, enabling hospitals to maintain their profitability.